Morphological Characterization of Sesame Germplasm in Semi-arid Condition of Delhi - Meena, Vijay Singh; Yadav, Rashmi; Raiger, H.L.; Singh, Kartar; Parimalan, R.; Shekhawat, Neelam; Gupta, Veena (Annals of Arid Zone, 2023)
The base line for sesame improvement is to evaluate that diversity amongtrait of importance. Total 696 germplasm of sesame conserved in gene bank of ICAR-NBPGR were evaluated for morphological traits under augmented block design duringkharif season of 2017-18 at ICAR-NBPGR Experimental Farm, Issapur and New Delhi.Analysis of variance revealed significant difference among genotypes for all the tencharacters studied. IC500816 found promising for early flowering (26 days) while verylate flowering observed in IC208657 (75 days). Higher yield per plant recorded inIC501018 (47.00 gm) and while maximum tallness recorded in IC204843 (226 cm). Highestno. of capsule per plant found in IC023271 (195.00) and maximum no. of locules percapsule identified in IC132182 (20). Violet- purple corolla and blackish seed observedin IC208662 genotype. Phenotypic coefficient of variation (PCV) found higher thangenotypic coefficient of variation (GCV) for most of the characters studied indicates therole of environmental variance in the total variance. High heritability was recorded forplant height and capsule per plant.